Психоаналіз у системі наратологічного аналізу - Натяжко, Світлана; Natyazhko, Svetlana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про важливість та актуальність дослідження психоаналітичного наративу. Наведено основні етапи становлення наратології як науки та подано різні дефініції наративу. Досліджено місце психоаналізу у системі наратологічного аналізу. Показано безпосередній зв'язок художнього наративу з психоаналізом із метою увиразнення доцільності вивчення художніх творів, написаних у стилі історій хвороб 3. Фройда як психоаналітичних наративів. На цій основі здійснено аналіз однієї з новел сучасної французької письменниці Анни Ґавальди з огляду на її наратологічну основу та психоаналітичне підґрунтя. Також у статті розглянуто одну з історій хвороб 3. Фройда як художній текст-наратив. Доведено наративну природу обох текстів. The article deals with the importance and relevance of the study of the psychoanalytic narrative. The main stages of the formation of narratology as a science are shown and various definitions of narrative are given. A particular attention is paid to the period of emergence of the term "postclassical narratology and the creating five paradigms of postclassical narratology on the basis of coming out of classical narratology. The place of psychoanalysis in the system of narrative analysis is studied and the preconditions for the emergence of link between a narratology and a psychoanalytic theory is examined. The direct connection between a literary narrative and a psychoanalysis is circled with the aim of underlining the feasibility of studying works of the fiction literature, written in the style of Freud's disease stories as psychoanalytic narratives. On this basis the analysis of one of the novels of the contemporary French writer Anna Gavalda is given here taking into consideration its narratology and psychoanalytic bases. In the article one of the stories recorded by the founder of classical psychoanalysis Freud during a psychotherapy treatment as a literary text-narrative is also dismantled and thereby its narrative nature is proved.
Psychoanalysis in the System of Narrative Analysis
Keywords: посткласична наратологія; психоаналіз; postclassical narratology; psychoanalysis